Nutritional status, symptom burden, and predictive validity of the Pt-Global web tool/PG-SGA in CKD patients: A hospital based cross sectional study. - Ishfaq Rashid; Pramil Tiwari; Sanjay D'Cruz; Shivani Jaswal (Public Library of Science (PLoS), 2023)
Background Despite not being frequently recognized, malnutrition, a consequence of chronic kidney disease, negatively affects morbidity, mortality, functional activity, and patient's quality of life. Management of this condition is made more difficult by the dearth of knowledge regarding the symptom burden brought on by inadequate nutritional status. Additionally, there are multiple tools to evaluate nutritional status in CKD; but, Pt-Global web tool/PG-SGA used in oncology, has not been investigated in chronic kidney disease patients. This study aimed to explore the nutritional status, symptom burden and also investigate the predictive validity of Pt-Global web tool/PG-SGA among pre-dialysis diabetic and non-diabetic chronic kidney disease patients. Methodology This cross-sectional study was carried out at a renal clinic of a tertiary care public teaching hospital. Nutritional status and symptom burden was evaluated by employing a 'Pt-Global web tool/PG-SGA' which is considered as a preeminent interdisciplinary tool in oncology and other chronic catabolic conditions. The predictive validity of the Pt-Global web tool/PG-SGA, referred as overall score for malnutrition was ascertained using Receiver Operating Curves (ROC). The conclusions were drawn using descriptive statistics, correlation, and regression analysis. Results In a sample of 450 pre-dialysis CKD patients, the malnutrition was present in 292(64.9%) patients. Diabetic CKD patients exhibit higher proportion of malnutrition 159(35.3%). The prevalence of malnutrition was exacerbated by eGFR reduction. The overall Pt-Global web tool/PGA-SGA score was significantly influenced by the symptoms of fatigue (81.5%), appetite loss (54.8%), physical pain (45.3%), constipation (31.78%), dry mouth (26.2%), and feeling full quickly (25.8%). The ROC analysis showed that the AUC for the total PG-SGA score was 0.988 (95% CI: 0.976-1.000), indicating that it is a reliable indicator of malnutrition. The sensitivity (84.2%) for identifying malnutrition was low when using the conventional tool cut off score of ≥9. Instead, it was discovered that a score of ≥3 had a greater sensitivity (99.3%) and specificity (44.3%) and was therefore recommended. Conclusions This study not only presents empirical evidence of poor nutritional status in CKD patients but also reveals that it is worse in patients with diabetes, hypoalbuminemia, and poorer kidney function (well recognized risk factors for cardiovascular disease). Early diagnosis and management of symptoms contributing malnutrition will reduce mortality and CKD progression. The Pt-Global web tool/PG-SGA total score of 3 or more appears to be the ideal cut off score for identifying malnutrition, which can be utilized by dietician for improving malnutrition.